AN ANALYSIS OF TEACHERS’ STRATEGIES IN IMPROVING STUDENTS’ VOCABULARY AT SMP NEGERI 2 TONDANO - Eliasar P., Febryan; Maru, Mister Gidion; Wongkar, Yapi H. (SoCul: International Journal of Research in Social Cultural Issues, 2024)
Vocabulary mastery is an essential aspect of learning English; therefore, appropriate learning strategies are needed to help students improve their understanding and effective use of vocabulary. In practice, the implementation of these strategies is inseparable from various challenges, making it important to examine how teachers apply vocabulary-learning strategies, the obstacles they encounter, and the efforts they make to overcome them. This study examines the strategies employed by teachers to improve students’ vocabulary, identifies the obstacles they face, and explains the methods used to address these challenges. A descriptive qualitative method was employed in this study, which was conducted at SMP Negeri 2 Tondano during the 2024/2025 academic year. The participants were two English teachers, and the data were collected through interviews and documentation. The collected data were analyzed using data condensation, data display, and conclusion drawing. The findings reveal that teachers use strategies such as translation, drills, memorization, singing, and games. The obstacles identified include limited instructional time, low student motivation, a lack of learning media, and variations in students’ language proficiency. To overcome these challenges, teachers adapt their strategies, create simple learning resources, and apply engaging instructional methods. In conclusion, effective teaching strategies play a crucial role in improving students’ vocabulary mastery. This research aims to provide guidance for teachers and researchers in developing more effective vocabulary-learning approaches. In addition, the findings offer practical insights that can support educators and schools in designing vocabulary instruction that is more responsive to students’ needs and classroom conditions.